Effectiveness of Standard Oral Care Plan During Hospital Stay in Individuals With Brain Injury - Kothari, Simple F.; Nascimento, Gustavo G.; Jakobsen, Mille B.; Nielsen, Jørgen F.; Kothari, Mohit (Frontiers in Neurology, 2021)
Objective: To investigate the effectiveness of an existing standard oral care program (SOCP) and factors associated with it during hospitalization in individuals with acquired brain injury (ABI). Material and Methods: A total of 61 individuals underwent a SOCP for 4 weeks in a longitudinal observational study. Rapidly noticeable changes in oral health were evaluated by performing plaque, calculus, bleeding on probing (BOP) and bedside oral examination (BOE) at weeks 1 and 5. Individuals' brushing habits, eating difficulties, and the onset of pneumonia were retrieved from their medical records. Association between oral-health outcomes to systemic variables were investigated through multilevel regression models. Results: Dental plaque (P = 0.01) and total BOE score (P < 0.05) decreased over time but not the proportion of dental calculus (P = 0.30), BOP (P = 0.06), and tooth brushing frequency (P = 0.06). Reduction in plaque and BOE over time were negatively associated with higher periodontitis scores at baseline (coef. −6.8; −1.0), respectively, which in turn were associated with an increased proportion of BOP (coef. ≈ 15.0). An increased proportion of calculus was associated with eating difficulties (coef. 2.3) and the onset of pneumonia (coef. 6.2). Conclusions: Nursing care has been fundamental in improving oral health, especially reducing dental plaque and BOE scores. However, our findings indicate a need for improving the existing SOCP through academic-clinical partnerships. Clinical Relevance: Early introduction of oral care program to brain-injured individuals is beneficial in reducing plaque accumulation and improving oral health.